IMPLEMENTASI MODEL KOOPERATIF TIPE PICTURE AND PICTURE PADA MATA PELAJARAN IPA - Nor Hapipah; Nur Inayah Syar; Sulistyowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research was motivated by the interest of researchers in using the implementation of the picture and picture type cooperative model in science lessons in class v. The purpose of this research is to see how the implementation of the learning model in the classroom. This type of research uses descriptive qualitative. The data analysis technique used in this study uses four stages, including 1) collecting data, 2) reducing data, 3) presenting data, and 4) drawing conclusions and verification. The implementation of the picture and picture type of cooperative learning model is applied according to the syntax. From the results of the study, it was found that the application of the cooperative model of the picture and picture type in science subjects had been applied as well as the teaching and learning process in general. The learning outcomes of science subjects using a picture and picture cooperative model have a value of 100% reaching the KKM. Some of the obstacles felt by the teacher at the time of learning can be resolved correctly.